Multigene Methylation Analysis And The Noninvasive Diagnosis Of Prostate Cancer From Body Fluids - Raluca, Dumache; Anca, Tudor; Daniela, Ionescu; Florin, Rogobete Alexandru; Razvan, Bardan (European Scientific Journal, ESJ, 2016)
Introduction During prostatic carcinogenesis, DNA hypermethylation occurs, thus representing a promising biomarker for the early detection of this malignancy. In our study, we aim to determine the usefulness of a molecular and multigene test for prostate cancer. However, this is based on the quantitative methylation-specific polymerase chain reaction (qMSP) of three genes from voided urine specimens by noninvasive methods. Materials and Methods In this study, the voided urine specimens were collected from 89 patients with prostate cancer and 69 controls. Genomic DNA was isolated and subjected to bisulfite modification. Consequently, we tested the methylation status of genomic DNA of three genes, namely: GSTP1, APC, and MDR1. This was done using the quantitative methylationspecific PCR method. Therefore, the obtained results were correlated with the clinicopathologic findings. Results Promoter methylation of GSTP1 gene in voided urine samples was found in 87 out of 89 (97.8%) PCa patients and in 13 out of 62 (21 %) BPH men. In APC gene, methylated levels have been found in 61 out of 89 (68.5%) PCa patients and in 8 out of 62 (12.9%) BPH men. MDR1 gene was found to be hypermethylated in 60 out of 89 (67.4%) PCa patients and in 4 out of 62 (6.5%) BPH men. In addition, we obtained a sensitivity of 88.99% and a specificity of 85.5% for the multigene panel. The AUC in this case was 0.927. Conclusion The analysis of a multigene panel of three methylated genes in prostate cancer by qMSP, can be used to distinguish between men with malignant and benign prostatic diseases from voided urine specimens. Also, it can be used for the follow-up of those men who are presenting increased risk of prostate cancer by noninvasive methods.